Autoimmune hepatitis: new in diagnostics, a pathogenesis and treatment - Ye. N. Shirokova; K. V. Ivashkin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To generalize new data on diagnostics, pathogenesis and treatment of autoimmune hepatitis (AIH).Original positions. AIH is a chronic inflammatory liver disease which is characterized by destruction of terminal plate by mononuclear infiltrate (interface hepatitis) according to histological investigation, hypergammaglobulinemia and production of autoantibodies. Genetic risk factors of AIH development is the presence of DRB1*0301 and DRB1*0401 alleles. Decrease of number and functional activity of CD4+CD25 + (regulatory) Т-cells leads to disorder of immunological homeostasis. Improvement of AIH treatment results is possible at continuation of corticosteroid treatment before normalization of liver tests and histological pattern, at early detection of «difficult» patients and carrying out of long-term maintenance therapy after the first relapse of disease. Alternative medical agents include calcineurin inhibitors, mycophenolate mofetil, and recombinant interleukin-10, abatacept and CD-3 specific antibodies. Liver transplantation is effictive treatment method.Conclusion. Improvement of corticosteroid treatment allows to determine candidates for alternative treatment. Budesonide is a drug of choice for the patients who were not receiving treatment before. Development of new treatment strategy is possible on the basis of assessment of key defects of immunological homeostasis and antigenic targets.